Kinetics of Electrochemical Removal of Nickel using Bio-electrochemical Reactor with Packed Bed Rotating Cylinder Cathode - Zahraa A.kadhim, Zahraa; H. Abbar, Ali (Al-Khwarizmi Engineering Journal, 2022)
The kinetics of nickel removal from aqueous solutions using a bio-electrochemical reactor with a packed bed rotating cylinder cathode was investigated. The effects of applied voltage, initial nickel concentration, the rotation speed of the cathode, and pH on the reaction rate constant (k) were studied. The results showed that the cathodic deposition occurred under mass transfer control for all values of the applied voltage used in this research. Accordingly, the relationship between concentration and time can be represented by a first-order equation. The rate constant was found to be dependent on the applied voltage, initial nickel concentration, pH, and rotation speed. It was increased as the applied voltage increased and decreased as the initial concentration increased. Its relation to the applied voltage can be fitted as follows:where ko =0.01695 min-1 and -β=0.431. pH and rotation speed have two dissimilar effects on the rate constant. Increasing the pH from 3-6 leads to an increase in the rate constant, while a decrease in the rate constant beyond pH=6 has occurred. Increasing the rotation from 100 to 300 rpm results in an increase in the rate constant. However, the rate constant decreases significantly beyond a rotation speed of 300 rpm.